The fundamental right to just administrative action: judicial review of administrative action in the democratic South Africa - Plasket, Clive (Rhodes University, Faculty of Law, Law, 2003)
For most of its existence South African administrative law has been shaped by the doctrine of parliamentary sovereignty "“ the heart of the constitutional order from 1910 to 1994 "“ and a racist political system that favoured the white minority at the expense of the black majority. In these circumstances, the rules of administrative law were of limited use in protecting the individual from exercises of administrative power that infringed fundamental human rights, often on a grand scale. On 27 April 1994, however, a new political and constitutional order came into existence that swept away the very foundations of the old order: parliamentary sovereignty was replaced by constitutional supremacy and the racial exclusivity of the old order was replaced by a commitment to equality, freedom and dignity in a democratic state. A justiciable Bill of Rights was at centre stage in this new order. That Bill of Rights includes a fundamental right to just administrative action. It is both the new constitutional order and this rather unusual fundamental right that have changed the nature of South African administrative law. This thesis examines the effect of the fundamental right to just administrative action on the law and practice of the judicial review of administrative action. It does so principally by examining the legal position before and after 27 April 1994 with particular reference to: what is meant by administrative action; the exercise of administrative power by private bodies regulated by the rules of administrative law, on the one hand, and exercises of private power regulated by rules of private law, on the other; the rules of standing, the notion of justiciability and the constitutionality of rules that seek to limit the right of the individual to approach a court to review administrative action; the meaning and scope of the right to lawful, reasonable and procedurally fair administrative action, in terms of the common law, the Constitution and the Promotion of Administrative Justice Act 3 of 2000; the meaning, scope and efficacy of the rights to reasons for administrative actions and of access to information; the procedure of judicial review and remedies that may be granted for the infringement of a person's right to just administrative action; and conclusions and recommendations with regard to progress made in the construction of South Africa's new, democratically based, administrative law.
Keywords: Judicial review of administrative acts -- South Africa; Administrative acts -- South Africa; Administrative law -- South Africa; Public administration -- South Africa